Pitfalls in the Diagnosis of Nodular Lymphocyte Predominant Hodgkin Lymphoma: Variant Patterns, Borderlines and Mimics - Younes, Sheren (Cancers (Basel), 2021)
SIMPLE SUMMARY: Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is a rare lymphoma containing infrequent tumor cells (LP cells) in a background of non-neoplastic cells. Some cases of NLPHL can recur or progress to a more aggressive lymphoma, such as diffuse large B-cell lymphoma. Awareness of the different appearances of NLPHL and its overlap with other lymphomas are important for the appropriate diagnosis, classification and research. This article discusses the conceptual framework and guidelines for the diagnosis of NLPHL, and how NLPHL can be best separated from its mimics. Emerging data in the field point to genetic changes in LP cells that are shaped by immune mechanisms. In addition, non-neoplastic cells in the background of LP cells also appear to play an important role. Further investigation is necessary to fully understand the biology of NLPHL and personalize cancer care for patients affected by this lymphoma. ABSTRACT: Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) represents approximately 5% of Hodgkin lymphoma and typically affects children and young adults. Although the overall prognosis is favorable, variant growth patterns in NLPHL correlate with disease recurrence and progression to T-cell/histiocyte-rich large B-cell lymphoma or frank diffuse large B-cell lymphoma (DLBCL). The diagnostic boundary between NLPHL and DLBCL can be difficult to discern, especially in the presence of variant histologies. Both diagnoses are established using morphology and immunophenotype and share similarities, including the infrequent large tumor B-cells and the lymphocyte and histiocyte-rich microenvironment. NLPHL also shows overlap with other lymphomas, particularly, classic Hodgkin lymphoma and T-cell lymphomas. Similarly, there is overlap with non-neoplastic conditions, such as the progressive transformation of germinal centers. Given the significant clinical differences among these entities, it is imperative that NLPHL and its variants are carefully separated from other lymphomas and their mimics. In this article, the characteristic features of NLPHL and its diagnostic boundaries and pitfalls are discussed. The current understanding of genetic features and immune microenvironment will be addressed, such that a framework to better understand biological behavior and customize patient care is provided.